Irrigation Scheduling As a Means of Applying the Right Water Amount and Monitoring Soil Moisture for Vegetable Crops Grown in Florida in the BMP Era - Eric Simonne; George Hochmuth (EDIS)
This publication is one of a series entitled Fertilizer and Irrigation Management in the BMP Era. This series is divided into nine principles described in the Introduction Chapter (HOS-897). This publication is part of Principle 5, "Irrigation Amount Must Reflect Crop Water Use ... No More, No Less." BMP implementation requires a global approach to production management. However, for presentation purposes, each aspect of vegetable production is described in a separate publication. This document is HS909, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2003.